WEBVTT
00:00:00.622 --> 00:00:03.342
A pendulum is taken from Earth to the Moon.
00:00:03.972 --> 00:00:11.292
Will the pendulum have a higher frequency, a lower frequency, or the same frequency on the surface of the Moon as on the surface of Earth?
00:00:12.702 --> 00:00:23.702
In order to answer this question, we first need to recall that the frequency of a pendulum, that is, the rate at which it oscillates from side to side, depends on the gravitational acceleration that the pendulum experiences.
00:00:24.182 --> 00:00:33.052
Specifically, the frequency of a pendulum can be calculated using this formula, where πΏ is the length of the pendulum and π is the local acceleration due to gravity.
00:00:33.372 --> 00:00:39.362
Now, often when weβre dealing with problems in mechanics, such as this one, we treat π as if itβs just a constant.
00:00:39.782 --> 00:00:43.782
Specifically, we tend to use a value of 9.81 meters per second squared.
00:00:44.002 --> 00:00:48.892
However, this value is just the standard gravitational acceleration near the surface of Earth.
00:00:49.332 --> 00:00:57.202
If we were to move away from the surface of the Earth or indeed to the Moon or a different planet, then weβd find that the local gravitational acceleration would be different.
00:00:57.662 --> 00:01:04.452
So to be precise, we should really call this quantity π sub e to signify that itβs the gravitational acceleration near the surface of the Earth.
00:01:06.142 --> 00:01:10.202
In this question, weβre asked to think about what would happen if we took this pendulum to the Moon.
00:01:10.832 --> 00:01:14.282
In this case, it will experience a different gravitational acceleration.
00:01:14.502 --> 00:01:15.682
Letβs call this π m.
00:01:16.262 --> 00:01:20.882
Now, the question doesnβt actually tell us what the gravitational acceleration is like on the surface of the Moon.
00:01:21.222 --> 00:01:24.232
However, we know that the Moon has a much lower mass than the Earth.
00:01:24.262 --> 00:01:27.812
And therefore, the gravitational acceleration on its surface will be lower.
00:01:28.122 --> 00:01:31.022
So we can say that π m is less than π e.
00:01:31.852 --> 00:01:37.972
We can see that taking our pendulum from the surface of the Earth to the surface of the Moon will decrease the value of π.
00:01:38.402 --> 00:01:42.932
And since weβre not changing the pendulum itself, we know that πΏ is effectively a constant.
00:01:43.342 --> 00:01:51.062
Since π is changing and everything else on the right-hand side of this formula is constant, this means that π, the frequency of the pendulum, must also change.
00:01:51.332 --> 00:01:54.642
So now at least we know that the frequency wonβt stay the same as when it was on Earth.
00:01:55.042 --> 00:02:01.792
However, looking at this formula, itβs not immediately obvious whether decreasing π will cause π to increase or decrease.
00:02:02.182 --> 00:02:14.802
In a situation like this, when weβre trying to determine how a change in one variable will affect another variable but we donβt have any numbers to work with, it can be useful to try to establish what type of proportionality exists between the two variables.
00:02:15.072 --> 00:02:17.502
For example, is π proportional to π?
00:02:18.152 --> 00:02:20.212
Could it be proportional to the square of π?
00:02:20.742 --> 00:02:22.592
How about inversely proportional to π?
00:02:23.092 --> 00:02:32.332
Establishing this type of relationship between the two variables π and π will enable us to easily see whether decreasing π will increase or decrease π.
00:02:32.782 --> 00:02:39.982
Now, for the sake of this question, where weβre not actually calculating an answer, letβs just assume that our approximately equal to sign is an equal sign.
00:02:40.412 --> 00:02:50.512
Now, to turn an equation like this one into a statement about proportionality, we can effectively remove all the constants in the equation and replace the equal sign with a proportional to sign.
00:02:51.002 --> 00:02:56.572
In this case, this gives us π is proportional to one over the square root of one over π.
00:02:56.822 --> 00:02:59.992
Now, this isnβt much clearer since we still have a fraction within a fraction.
00:03:00.242 --> 00:03:02.582
However, using algebra, we can clear some of this up.
00:03:02.962 --> 00:03:04.742
Firstly, letβs deal with the square root sign.
00:03:05.202 --> 00:03:10.542
The square root of one over π is equivalent to the square root of one over the square root of π.
00:03:11.052 --> 00:03:13.592
And the square root of one is of course just one.
00:03:14.012 --> 00:03:17.762
We can now see that we have one over one over the square root of π.
00:03:18.172 --> 00:03:22.512
In other words, we have the reciprocal of the reciprocal of the square root of π.
00:03:23.332 --> 00:03:27.962
Taking the reciprocal over reciprocal in this way just leaves us with the quantity that we started with.
00:03:28.212 --> 00:03:30.302
And in this case, thatβs the square root of π.
00:03:31.242 --> 00:03:35.592
This shows us that the frequency π is proportional to the square root of π.
00:03:35.962 --> 00:03:40.852
Now that weβve obtained a nice, simple proportionality statement like this, our problem becomes much simpler.
00:03:41.142 --> 00:03:46.742
When we move our pendulum from the Earth to the Moon, we know that the size of π is decreased.
00:03:47.052 --> 00:03:50.982
And if we decrease the size of π, then we decrease the size of the square root of π.
00:03:51.502 --> 00:03:55.592
Since π is proportional to the square root of π, this means that π must decrease too.
00:03:56.112 --> 00:03:59.832
In other words, we find that the pendulum has a lower frequency on the Moon than it did on the Earth.
00:04:00.302 --> 00:04:01.882
And this is the final answer to our question.
00:04:02.082 --> 00:04:08.662
If a pendulum is taken from the Earth to the Moon, the pendulum will have a lower frequency on the surface of the Moon as on the surface of the Earth.